Pig models of neurodegenerative disorders: Utilization in cell replacement‐based preclinical safety and efficacy studies. Issue 12 (12th April 2014) - Dolezalova, Dasa; Hruska‐Plochan, Marian; Bjarkam, Carsten R.; Sørensen, Jens Christian H.; Cunningham, Miles; Weingarten, David; Ciacci, Joseph D.; Juhas, Stefan; Juhasova, Jana; Motlik, Jan; Hefferan, Michael P.; Hazel, Tom; et al.
ABSTRACT An important component for successful translation of cell replacement‐based therapies into clinical practice is the utilization of large animal models to conduct efficacy and/or safety cell dosing studies. Over the past few decades, several large animal models (dog, cat, nonhuman primate) were developed and employed in cell replacement studies; however, none of these models appears to provide a readily available platform to conduct effective and large‐scale preclinical studies. In recent years, numerous pig models of neurodegenerative disorders were developed using both a transgenic approach as well as invasive surgical techniques. The pig model (naïve noninjured animals) was recently used successfully to define the safety and optimal dosing of human spinal stem cells after grafting into the central nervous system (CNS) in immunosuppressed animals. The data from these studies were used in the design of a human clinical protocol used in amyotrophic lateral sclerosis (ALS) patients in a Phase I clinical trial. In addition, a highly inbred (complete major histocompatibility complex [MHC] match) strain of miniature pigs is available which permits the design of comparable MHC combinations between the donor cells and the graft recipient as used in human patients. Jointly, these studies show that the pig model can represent an effective large animal model to be used in preclinical cell replacement modeling. This review summarizes the available pig models of neurodegenerative disorders and the use of some of these models in cell replacement studies. The challenges and potential future directions in more effective use of the pig neurodegenerative models are also discussed. J. Comp. Neurol. 522:2784–2801, 2014. © 2014 Wiley Periodicals, Inc.